MODELING AND SIMULATION PROCESS OF EXTRACTION ESSENTIAL OILS BY STEAM DISTILLATION - Armijo C., J. (2012)
This paper presents an investigation of the extraction of essential oils by steam distillation. The process is analyzed and a model is developed for the extraction of essential oil of eucalyptus in pilot scale with a steam flow of 5.73 g / min. According to the model Dunckhorst-Houghton, which considers the effect of axial dispersion, and the use of optimization procedures to establish the model parameters, excellent agreement was obtained between the amount of oil extracted theoretical and experimental.